A comparative assessment of human exposure to tetrabromobisphenol A and eight bisphenols including bisphenol A via indoor dust ingestion in twelve countries - Wang, Wei; Abualnaja, Khalid O.; Asimakopoulos, Alexandros G.; Covaci, Adrian; Gevao, Bondi; Johnson-Restrepo, Boris; Kumosani, Taha A.; Malarvannan, Govindan; Minh, Tu Binh; Moon, Hyo-Bang; Nakata, Haruhiko; Sinha, Ravindra K.; et al. (Environment international, 2015)
Tetrabromobisphenol A (TBBPA) and eight bisphenol analogues (BPs) including bisphenol A (BPA) were determined in 388 indoor (including homes and microenvironments) dust samples collected from 12 countries (China, Colombia, Greece, India, Japan, Kuwait, Pakistan, Romania, Saudi Arabia, South Korea, U.S., and Vietnam). The concentrations of TBBPA and sum of eight bisphenols (ƩBPs) in dust samples ranged from <1 to 3600 and from 13 to 110,000ng/g, respectively. The highest TBBPA concentrations in house dust were found in samples from Japan (median: 140ng/g), followed by South Korea (84ng/g) and China (23ng/g). The highest ∑BPs concentrations were found in Greece (median: 3900ng/g), Japan (2600ng/g) and the U.S. (2200ng/g). Significant variations in BPA concentrations were found in dust samples collected from various microenvironments in offices and homes. Concentrations of TBBPA in house dust were significantly correlated with BPA and ∑BPs. Among the nine target chemicals analyzed, BPA was the predominant compound in dust from all countries. The proportion of TBBPA in sum concentrations of nine phenolic compounds analyzed in this study was the highest in dust samples from China (27%) and the lowest in Greece (0.41%). The median estimated daily intake (EDI) of ∑BPs through dust ingestion was the highest in Greece (1.6–17ng/kgbw/day), Japan (1.3–16) and the U.S. (0.89–9.6) for various age groups. Nevertheless, in comparison with the reported BPA exposure doses through diet, dust ingestion accounted for less than 10% of the total exposure doses in China and the U.S. For TBBPA, the EDI for infants and toddlers ranged from 0.01 to 3.4ng/kgbw/day, and dust ingestion is an important pathway for exposure accounting for 3.8–35% (median) of exposure doses in China. •TBBPA and bisphenols were measured in 388 indoor dust samples from 12 countries.•The contribution of house dust to daily intakes of TBBPA and BPA varied among countries.•Dust is an important source of TBBPA exposures in China, Japan and South Korea.•Dust ingestion accounted for 3.8–35% (median) of TBBPA exposure in China.•Contribution of dust to BPA intake is minor.